Varicella Induced Cerebellitis in an Adult: Case Report - Ustun, Suzan; Ustun, Cemal; Demir, Caner Feyzi (Ortadogu Ad Pres & Publ Co, 2012)
Cerebellitis developing due to Varicella zoster virus infection is a very rare complication in adults. A 19-year-old male patient who was admitted to outpatient clinic was hospitalized with complaints of headache, dizziness, ataxia, mental alienation and speech impairment started five days ago following widespread body rashes related to VZV. VZV IgM and IgG antibodies were detected on cerebrospinal fluid (CSF) examination. Also VZV DNA was found positive with polymerase chain reaction (PCR) in CSF. The patient was diagnosed as VZV-induced cerebellitis based on clinical and laboratory findings. Only symptomatic treatment was started as acyclovir could not be provided. The patient fully recovered with symptomatic treatment. In this case, VZV induced cerebellitis was seen to improve with only symptomatic treatment without administering antiviral treatment.
Varicella induced cerebellitis in an adult: Case report
Keywords: Herpesvirus 3, human; cerebellar diseases; chickenpox; therapy